Diterpenoids from the stems of Tripterygium hypoglaucum (Celastraceae) and cytotoxic evaluation. (June 2015) - Li, Xiao-Lei; Gao, Ling-Huan; Li, Hong-Mei; Wang, Li-Ting; Lee, Kuo-Hsiung; Li, Rong-Tao
Graphical abstract: Four new diterpenoids (1 –4 ), along with seven known ones (5 –11 ), were isolated from Tripterygium hypoglaucum . Triptolide (5 ) and 2-epitripdiolide (6 ) showed significant anti-tumor activity. Highlights: Eleven diterpenoids were isolated including four new ones. The structures of the four new diterpenoids were determined. Anti-tumor, anti-inflammatory and anti-HIV activities of compounds were evaluated. Triptolide (5 ) and 2-epitripdiolide (6 ) showed significant cytotoxicity. Abstract: Four new diterpenoids, 2α, 16α-hydroxy- ent -kauran-19, 20-olide (1 ), isopimara-8(14), 15-diene-11β, 19-diol (2 ), isopimara-8(14), 15-diene-12α, 19-diol (3 ), and 3-oxo-14, 15-dihydroxyabieta-8, 11, 13-trien-19-ol (4 ), along with seven known compounds (5 –11 ) were isolated from Tripterygium hypoglaucum . Their structures were established on the basis of extensive spectroscopic analysis. Triptolide (5 ) and 2-epitripdiolide (6 ) showed significant cytotoxicity against A549, DU145, KB, KBvin and MDA-MB-231 cell lines with IC50 values of 0.0012–0.1306 μM in vitro .